KUALITAS PAPAN PARTIKEL DARI CAMPURAN AMPAS TEBU DAN PARTIKEL MAHONI DENGAN BERBAGAI VARIASI KADAR PEREKAT PHENOL FORMALDEHIDA - Ivan Mikael; Rudi Hartono; Tito Sucipto (Program studi Kehutanan USU, 2015)
The purpose of this study was to evaluate the effect of variations in the composition of bagasse and mahogany’s particle with phenol formaldehyde adhesive variation levels on quality particle board also to determine the best treatment. The dimension of sample test was 25x25x1 cm with a density target of 0.7 g/cm3. The composition between bagasse and mahogany’s particle were 60:40, 70:30, and 80:20. While for the PF adhesive level were 10%, 12.5%, and 15%. The results showed that density, moisture content, water absorption for 2 hours and 24hours, thickness swelling for 2 hours and 24 hours, MOE, MOR, and IB were 0.57-0.64 g/cm3, 8.40-12.64%, 29.44-91.41% and 55.50-123.28%, 5.68-18.33% and10.26-32.34%, 3893-9475 kg/cm2, 51.88-106.23 kg/cm2, and 0.49-0.71 kg/cm2. Statistical analysis in this research used factorial randomized completed design and the results were compared with JIS A 5908-2003 standard. The result showed that some of the test on particle board not fulfilled the standard, such as internal bond and MOE. However, all of density and moisture content had fulfilled the standard. Thickness swelling test on particle board composition of 80:20 and adhesive content of 15% had fulfilled standard. MOR test on particle board composition of 80:20 and adhesive content of 10% as well as composition of 60:40 and adhesive content of 12,5% had fulfilled standard. The best result of treatment from this research was a partcle board made from composition of 80:20 and 10% levels of PF adhesive. Keywords:particleboard, bagasse, mahogany, adhesive content, phenolformaldehyde